Designs treatment of the internal spaces of pharmacies (Al-Academy, 2024)
The pharmacy is the face for the health buildings and hospitals, The linking professional relationships and functional, it is been from the important places that most people go it, so according to that we must format its interior design in form that suitable with the need of most people use it or work in it, and this the search goal, dashing from the search subject which to hide finding designer treatment for the pharmacies interior spaces, to give share in the functional improvement performance or aesthetic. We define the search goals to share in educate the pharmacist in the effect of interior design for improvement of interior environment, in addition to the search consider as designer trying add to the other trying the interior design, and to open knowledge wanderer for searcher in this specialization. In the second chapter II contain the theoretical framework which it included two sections, the first unit contain the interior spaces for pharmacies which contain the nature of these spaces and then attributes. The second section contains the organization spaces for pharmacies, and spatial relationships and motional. The third chapter contains the search from method and search society and the search intent sample, and the search tool used in and it is analyzing form, and then descript the sample and analyzing it. And later contain the fourth chapter the result which search reach to it through analyzing, then the conclusions with the proposal and recommendations.